THE ROLE OF DECENTRALIZATION AND LOCAL ACTION IN THE CONTEXT OF GLOBALIZATION - Guamba, José Manuel Elija (International Journal of Research -GRANTHAALAYAH, 2018)
This article aims to analyze some of the processes that contributed to the emergence of theorizing about local development, namely, the Keynesian model crisis and aggravated social problems after the fall of the welfare State, globalization, and the role local action, decentralization and local government in the process of seeking of local development with the participation of civil society. Among the factors that contributed to the social crisis that led to the emergence of new theories of development, we have the collapse of the welfare State and the process that ended in neo-liberalism and globalization. It was in this context that new social actors with a new paradigm, that and the Local development process. Thus, arises the civil society, composed of entities that aim to develop through socio-economic dimension alternatives and environmental preservation. The process of globalization has not solved the social and economic problems of the contemporary world, in contrast, has contributed to further increase the differences between developed countries and those in development, leading many times, the growth of poverty and social exclusion. On the other hand, he is responsible for a process of local development institutions, bringing new perspectives to the adequacy of national public policies at regional/local peculiarities and the urban and rural spaces, in your physical, economic dimension, social and cultural. This process comes calling into question many traditional structures and public institutions as to your fitness and your performance in the management of economic and social policies, creating a dichotomy arising out of the policy challenges for the construction of a local network of care and social inclusion, with the participation of the communities.